Comparisons between three disciplines regarding device usage in a lecture theatre, academic performance and learning. Issue 1 (1st January 2020) - Limniou, Maria; Duret, Denis; Hands, Caroline
ABSTRACT: This investigation explored students' learning behaviour from three different disciplines in relation to the student personal device usage in a lecture theatre environment and its impact on learning and academic performance. 163 Psychology, 253 Life Sciences and 83 Veterinary Science students participated in this study by completing a questionnaire. Differences between the three disciplines have been identified regarding the device usage, (non)/learning activities and multitasking in a lecture theatre. The findings of this investigation contradict previously published literature regarding the student academic performance and the use of their own devices in a lecture theatre, as there was no difference amongst the students from the same discipline. Student learning experience is linked to their individual learning characteristics which may be connected to course characteristics and teaching approach. This study raises questions about the students' behaviour to bring their own devices in a lecture theatre and its implication on multitasking and teaching approaches.